Analisa Highest And Best Use pada Vacant Land di KM 6,5 Jalan Soekarno-Hatta Balikpapan - Raftonado Situmorang; Rifqi Dhani Hariyanto; Agung Prabowo; Oryza Lhara Sari (Jurnal Proyek Teknik Sipil, 2026)
Analysis of Highest and Best Use of Vacant Land at Soekarno-Hatta Kilo 6.5 Balikpapan City. The use of land as a building or property must be analyzed to get the maximum profit from the building. There is a vacant land located at Jalan Soekarno- Hatta Kilo 6.5 with an area of 9,500 m2 and located in the northern part of Balikpapan City. However, this vacant land is only used as a night market, whereas vacant land has a high probability to be renewed. Highest and Best Use analysis is conducted in order to get the probability of suitable property type based on the highest and best land value. This analysis uses four aspects that must be analyzed, namely physically possible to be established, legally permitted, economically feasible, and has the highest possible productivity. Determination of property alternatives begins with the distribution of questionnaires involving several stakeholders. In the results of the questionnaire, alternative properties were obtained, namely residential properties, hotels and apartments. Physical aspects consist of land location, land shape and size, public facilities and accessibility to the land location. Legal aspect consists of zoning and building code which refers to the regulation of Balikpapan City Regional Spatial Plan and One Map One Data website. Financial aspect consists of investment cost, property income, property expenditure, money flow in and out, and Net Present Value. In the aspect of maximum productivity, it is obtained that the hotel property provides the highest land value of Rp. 36,560,342 from the initial land price of Rp. 5,000,000 and provides a land productivity of 631%. It can be concluded that the hotel property alternative is a suitable property to be built on this land.